Influence of tool eccentricity on the material flow and microstructural properties of AA6061 aluminum alloy friction stir welds - Luqman Hakim, Ahmad Shah; Midawi, Abdelbaset R. H.; Walbridge, Scott; Gerlich, Adrian (Elsevier Ltd, 2020)
The effect of tool eccentricity on friction stir welding of AA6061-T651 aluminum alloy plates is evaluated. Microstructural characterization reveals that surface roughness of the weld bead is increased, while material flow and mixing in the stir zone is enhanced with increasing tool eccentricity. Moreover, grain size of examined regions are refined with increased tool eccentricity. Softening at the lower region of the stir zone was observed using both an aligned and 0.2 mm eccentric setup, where a high density of platelet-shaped precipitates are present.